BENCHMARKING EFISIENSI KINERJA HOTEL DI ERA PEMULIHAN PARIWISATA DENGAN PENDEKATAN DEA - Cucu Hayati; Leonard Adrie Manafe (JURNAL ILMIAH EDUNOMIKA, 2026)
This study evaluated the efficiency of hotel performance in Indonesia in the post-pandemic tourism recovery era during 2022-2025 as well as identify issuers that can be a reference for best practices through benchmarking instruments. The research method used a quantitative approach with the non-parametric Data Envelopment Analysis (DEA) method. The number of DMUs in this study is 9 hotel issuers listed on the Indonesia Stock Exchange (IDX), namely EAST, PWON, SHID, PSKT, DFAM, SNLK, BUVA, FITT, and JIHD. This study specifically applies the Variable Returns to Scale (VRS) model with an output-oriented approach to measure pure technical efficiency without bias from the influence of the operating scale. The results show that in the 2022–2024 period, the majority of hotel issuers managed to achieve full efficiency, but this number will decrease in 2025 as operational costs increase and market conditions change. The average pure technical efficiency of the industry was recorded to have decreased from the range of 95–96% in the initial period to 85.7% in 2025. EAST and PWON issuers have consistently been identified as the main references for other issuers that are not yet efficient. Through slack analysis, it was found that inefficiencies in issuers that are not optimal generally come from excess room capacity and the amount of labor that is disproportionate to the output produced. Based on these findings, the study recommends downsizing strategies for hotels in conditions of decreasing returns to scale and expansion strategies for hotels in conditions of increasing returns to scale to achieve better economies of scale efficiency.